2006
DOI: 10.1890/1540-9295(2006)004[0027:teoapd]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of amphibian population declines on the structure and function of Neotropical stream ecosystems

Abstract: Amphibians can be important consumers in both aquatic and terrestrial habitats and may represent an important energetic link between the two, particularly in the tropics, where amphibian species richness and abundance are high. In the past 20 years, amphibian populations have declined dramatically around the world; numbers have decreased catastrophically in protected upland sites throughout the neotropics, usually resulting in the disappearance of over 75% of amphibians at a given site, particularly those spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
245
1
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(264 citation statements)
references
References 15 publications
4
245
1
14
Order By: Relevance
“…Amphibian populations are declining globally, and many factors have been implicated in die-offs, including habitat loss or fragmentation, toxins, and pathogens (Daszak et al, 2000;Whiles et al, 2006;Becker et al, 2007). Further, we hypothesized that anthropogenic stressors, such as cattle grazing wetlands, may make amphibians more susceptible to infections because of immune system suppression Gray et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Amphibian populations are declining globally, and many factors have been implicated in die-offs, including habitat loss or fragmentation, toxins, and pathogens (Daszak et al, 2000;Whiles et al, 2006;Becker et al, 2007). Further, we hypothesized that anthropogenic stressors, such as cattle grazing wetlands, may make amphibians more susceptible to infections because of immune system suppression Gray et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to these dimorphic differences, body condition was similar across all species at both locations. This measurement was desired as snakes of the genus Sibon are snakes potentially affected by trophic disruption in areas where amphibian populations have declined (Whiles et al 2006). We attribute these dimorphic anomalies to the small sample size in our data, but also consider that little is known about the genus and that our numbers encountered may reflect the relative abundance of individuals given our efforts in surveying.…”
Section: Morphologymentioning
confidence: 98%
“…Recent research by Whiles et al (2006) has suggested that when a forest is affected by amphibian decline this could present a threat to populations of snakes from the reduction of available prey. Sibon, Dipsas, Sibynomorphus, and Tropidodipsas are genera potentially affected by this trophic disruption and because of this we recommend that herpetologists collaborate further on the snakes' population ecology and continue to monitor their presence and health across all Neotropical countries.…”
Section: Abundance and Habitatmentioning
confidence: 99%
“…In response to these high levels of decline and extinction, international initiatives (e.g., Amphibian Conservation Action Plan [ACAP], Gascon et al 2007; Global Amphibian Assessment [GAA], Stuart et al 2004) have called for the implementation of long-term monitoring and assessment around the world (Blaustein et al 1994) to determine the factors causing these declines. This increasing concern for anuran extinctions is not surprising because the loss of anuran populations and species could disrupt important ecosystem processes such as energy flow and food web dynamics (e.g., Ranvestel et al 2004, Gibbons et al 2006, Whiles et al 2006. Moreover, anurans are considered good bioindicators, and the condition of their populations is a warning to us about the status of ecosystems (Hayes et al 2002, Halliday 2008.…”
Section: Introductionmentioning
confidence: 99%